2017
DOI: 10.1097/pts.0000000000000456
|View full text |Cite
|
Sign up to set email alerts
|

Involvement in Root Cause Analysis and Patient Safety Culture Among Hospital Care Providers

Abstract: Background:The experience feedback committee (EFC) is a tool designed to involve medical teams in patient safety management, through root cause analysis within the team. Objective:The aim of the study was to determine whether patient safety culture, as measured by the Hospital Survey on Patient Safety Culture (HSOPS), differed regarding care provider involvement in EFC activities.Methods: Using the original data from a cross-sectional survey of 5064 employees at a single university hospital in France, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…For example, the staff interviewed raised the possibility of decentralizing risk management in hospital departments by promoting programs directly involving the medical teams in patient safety, such as experience feedback committees and the morbidity and mortality conferences. [ 23 , 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…For example, the staff interviewed raised the possibility of decentralizing risk management in hospital departments by promoting programs directly involving the medical teams in patient safety, such as experience feedback committees and the morbidity and mortality conferences. [ 23 , 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…5 Hitachinaka General Hospital, Ibaraki, Japan. 6 Department of Common Fundamental Nursing, Iwate Medical University School of Nursing, Iwate, Japan.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Patient safety culture is a product of individual and group values, attitudes, perceptions, competencies, and behavior patterns that determines the commitment as well as the style and proficiency of an organization's health and safety management [2]. Patient safety education and training [3,4] as well as utilization of Team Strategies and Tools to Enhance Performance and Patient Safety [5] and root cause analysis [6] are useful for improving patient safety culture. We have reported that long working hours of nurses may deteriorate their patient safety culture [7], and two studies in China and a study in Korea have also reported same results [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] In another study, we analyzed the association between patient safety culture, as measured by the Hospital Survey on Patient Safety Culture (HSOPS), and the care provider involvement in EFC activities. [ 9 ] We showed that EFC participants had a more highly developed patient safety culture, with nine of the 12 HSOPS dimension scores significantly higher than EFC non-participants. The three largest differences in the HSOPS score were related to the “feedback and communication about error”, organisational learning” and “non-punitive response to error” dimensions.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study reported a favourable association between involvement in EFC activities and the patient safety culture among hospital care providers. [ 9 ] Moreover, several studies have reported promising adherence of medical teams involved in EFC in emergency, psychiatry and pharmacy departments. [ 10 12 ] However, these studies identified several limitations related to the initial EFC framework.…”
Section: Introductionmentioning
confidence: 99%